Problems of formation of tourist-recreational complex in Irkutsk Region - Gafarova, Elena (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2010)
The key direction of economic development of Irkutsk region is forming a recreational complex based on such a unique resource as the lake Baikal as a competitive advantage of the region. It is possible to develop various kinds of tourism here.Development of the tourist sector may become one of the prime projects of development of interregional cooperation within the limits of the Siberian federal district. There exists a decision of Federal authorities to create in the Irkutsk region a special economic zone of tourist-recreational type, «The Gate of Baikal».The basic problem is that the material base of the sector has been essentially obsolete and does not correspond to the international standards. The airport «Irkutsk» is one of the bottlenecks.Another problem is alignment of seasonal prevalence of tourist flows. In the tourist sector, the practice of private-state partnership seems to be quite effective.